Adaptive Evolution of Genes Involved in the Regulation of Germline Stem Cells in Drosophila melanogaster and D. simulans. - Flores, H.A.; DuMont, V.L.; Fatoo, A.; Hubbard, D.; Hijji, M.; Barbash, D.A.; Aquadro, C.F. (G3 : genes - genomes - genetics, 2015)
Population genetic and comparative analyses in diverse taxa have shown that numerous genes involved in reproduction are adaptively evolving. Two genes involved in germline stem cell regulation, bag of marbles (bam) and benign gonial cell neoplasm (bgcn), have been shown previously to experience recurrent, adaptive evolution in both Drosophila melanogaster and D. simulans. Here we report a population genetic survey on eight additional genes involved in germline stem cell regulation in D. melanogaster and D. simulans that reveals all eight of these genes reject a neutral model of evolution in at least one test and one species after correction for multiple testing using a false-discovery rate of 0.05. These genes play diverse roles in the regulation of germline stem cells, suggesting that positive selection in response to several evolutionary pressures may be acting to drive the adaptive evolution of these genes.